Why is the Number of Patients of Methadone Maintenance Therapy in Indonesia Stagnant? Improvement of Service - Wulansari, W; Rahmaniati Makful, M (KnE Life Sciences, 2019)
At first, Methadone Maintenance Therapy Program (MMTP) was created to handle the increasing problem of HIV caused by used drug through injection. The spread of HIV through the needle is so fast that requires a comprehensive therapy effort. In 2003, Indonesia made a project pilot at drug dependence hospital in Jakarta and public hospital in Bali. The results of the project had positive impacts. There was behavior changing to stop using drugs. MMTP was firstly launched in 2006. The program used methadone dosage of liquid by drinking. The implementation of MMTP in Indonesia wasn’t maximized. Based on data from the Ministry of Health in 2015, the number of active patients was 2,300 and in 2013, there was 2,457. There was a decrease in the number of patients in the two years amounted to 6.38%. The research method used quality research by literature review and an in-depth interview with IDUs. The subjects of study had improvements of methadone services and evaluation of the therapeutic program implementation. The results of the research had a non-compliance with service guidelines, lack of psychosocial services, the performance of officers not optimal, and there were external influences on the adherence of patients — the conclusion needed capacity building, the involvement of stakeholders in this program, monitoring client through task shifting of an officer. Keywords: Methadone; drugs; HIV; IDU